2022
DOI: 10.3390/jfmk7010018
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular to Intracellular Body Water and Cognitive Function among Healthy Older and Younger Adults

Abstract: Compromised cognitive function is associated with increased mortality and increased healthcare costs. Physical characteristics including height, weight, body mass index, sex, and fat mass are often associated with cognitive function. Extracellular to intracellular body water ratio offers an additional anthropometric measurement that has received recent attention because of its association with systemic inflammation, hypertension, and blood–brain barrier permeability. The purposes of this study were to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, they might not yet have substantial changes in physical activity or nourishment and thus did not experience solid changes in body composition. Furthermore, age was reported to be an important factor to influence the fluctuation of cellular water distribution, such that ECW to ICW ratio increases with age and might be due to the steeper decrease in the ICW content than in the ECW compartment ( 9 , 50 ). After controlling for age and other covariates, most body composition variables became insignificant; only segmental BIA variables such as resistance and reactance in the lower extremities and the related body composition/water compartment variables such as SL_lower and SW_lower remained to be significantly associated with the incidence of MCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they might not yet have substantial changes in physical activity or nourishment and thus did not experience solid changes in body composition. Furthermore, age was reported to be an important factor to influence the fluctuation of cellular water distribution, such that ECW to ICW ratio increases with age and might be due to the steeper decrease in the ICW content than in the ECW compartment ( 9 , 50 ). After controlling for age and other covariates, most body composition variables became insignificant; only segmental BIA variables such as resistance and reactance in the lower extremities and the related body composition/water compartment variables such as SL_lower and SW_lower remained to be significantly associated with the incidence of MCI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, MCI patients of both sexes had just a slightly lower phase angle than the normal controls, and this difference disappeared after controlling for covariates in both women and men; the muscle quality expressed by phase angle might not be a sensitive marker of cognitive impairment in its early stage. Moreover, ECW/ICW is another sensitive parameter that is positively correlated with age as well as cognitive function such as executive function, inhibition, or attention ability in elderly people ( 9 , 50 ). In this study, after controlling for age, sex and the comorbidities, ECW/ICW in upper and lower extremities showed a tendency of associations with MCI prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two cross-sectional studies in patients of type 2 diabetes and in healthy elderly participants respectively showed that higher ECW/TBW or ECW/ICW was independently associated with poorer cognitive function. 23,24 However, the data from us and another study suggested that no significant association between cognitive function and ECW or ECW/ TBW. 25 This discrepancy might be related to the instability of fluid status in HD patients, different races, and different cognitive assessment methods.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, we found an abnormal cellular water distribution as demonstrated by the decrease in ICW_ECW ratio in CP individuals compared to the non-CP individuals. ICW_ECW has been considered a prognostic factor of several pathological conditions such as edema, sarcopenia, cancer, and cognitive decline, and is associated with muscle strength and gait speed in older populations ( 27 , 63 66 ). Decreased ICW_ECW suggests more serious reduction in the intracellular area water compared to that in the extracellular space and might have been caused by the lower BCM, body cell volume, or a malnutrition status in the CP individuals.…”
Section: Discussionmentioning
confidence: 99%